Left Jordan -Centralizer on Completely Prime -Ring (Journal of the College of Basic Education, 2022)
Let M be G-ring this research introduce the concepts of left (resp. right)-centralizer, left (resp. right) Jordan -centralizer, left (resp. right) Jordan triple -centralizer of G-ring as well as prove that every left (resp. right) Jordan -centralizer of completely prime G-ring M is left (resp. right)-centralizer of M.Mathematics Subject Classification: 16W25,16A12, 16A78.